PERKEMBANGAN FUNGSI PRAGMATIK PADA ANAK USIA 2,5 TAHUN (STUDI KASUS PADA AZZA AQILA JIHAN SYUASABITHA) - Ali Kusno (Kadera Bahasa, 2017)
The golden age of kid was a sensitive period. During this period, the kid was specially receiving the stimulant from theenvironment. The period of kid’s language development was various, dependent on the characteristics. This study relatedto the function development of kid’s language. The example case to the girl 2,5 years old, Azza Aqila Jihan Syuasabitha(Jihan). Jihan was growing in the family environment and child caring. The kid’s language was developing quickly. Theusage of language was devoted to Jihan’s interaction with family members. Collecting data method in this study was theobservation. The subject in this study was the child’s author. This study aimed to describe the development of Jihan’sspeech as child 2,5 years old based on the language function grouping according to M.A.K Halliday. The result of thestudy showed the kid can apply all of language function usage. Those are the instrumental, the regulatory, the interactional,the personal, the heuristic, the imaginative, and the representational. Therefore, she was interpreted has the ability aboveaverage the children the same age. The achievement was influenced by biological factors (parents who have good languageskills) and social environment (in the house, in the school, and so on) which can stimulate Jihan’s language development AbstrakMasa keemasan anak merupakan periode sensitif (sensitive periods). Selama masa tersebut anak secarakhusus mudah menerima stimulus-stimulus dari lingkungan. Tempo perkembangan bahasa anakcenderung variatif tergantung karakteristik anak. Penelitian ini berhubungan dengan perkembanganfungsi bahasa anak. Contoh kasus, Azza Aqila Jihan Syuasabitha (Jihan) anak perempuan yang berusia2,5 tahun. Jihan besar dalam lingkungan keluarga dan taman penitipan anak. Perkembangan fungsibahasanya pesat. Pemakaian bahasa dikhususkan pada interaksi Jihan dengan anggota keluarga.Pengumpulan data dalam penelitian dengan teknik pengamatan berperan serta. Subjek penelitian iniadalah anak penulis sendiri. Penelitian ini bertujuan untuk mendeskripsikan perkembangan tuturanJihan sebagai anak yang berusia 2,5 tahun berdasarkan pengelompokan fungsi bahasa menurut M.A.KHalliday. Hasil penelitian menunjukkan anak itu mampu menerapkan keseluruhan fungsi penggunaanbahasa, yakni instrumental, regulatoris/dogmatis, interaksional, personal, heuristik, imajinatif, danrepresentasional. Dengan demikian, dapat diinterpretasikan bahwa anak itu memiliki kemampuan diatas rata-rata anak seumur dia. Pencapaian tersebut dipengaruhi oleh faktor biologis (orang tua yangmemang memiliki kemampuan berbahasa yang baik) dan lingkungan sosial (di rumah, sekolah, dantempat lain).